Localization of drug biodistribution in a 3D-bioengineered subcutaneous neovascularized microenvironment. (December 2022) - Capuani, Simone; Hernandez, Nathanael; Paez-Mayorga, Jesus; Dogra, Prashant; Wang, Zhihui; Cristini, Vittorio; Chua, Corrine Ying Xuan; Nichols, Joan E.; Grattoni, Alessandro
Abstract: Local immunomodulation has shown the potential to control the immune response in a site-specific manner for wound healing, cancer, allergy, and cell transplantation, thus abrogating adverse effects associated with systemic administration of immunotherapeutics. Localized immunomodulation requires confining the biodistribution of immunotherapeutics on-site for maximal immune control and minimal systemic drug exposure. To this end, we developed a 3D-printed subcutaneous implant termed 'NICHE', consisting of a bioengineered vascularized microenvironment enabled by sustained drug delivery on-site. The NICHE was designed as a platform technology for investigating local immunomodulation in the context of cell therapeutics and cancer vaccines. Here we studied the ability of the NICHE to localize the PK and biodistribution of different model immunomodulatory agents in vivo. For this, we first performed a mechanistic evaluation of the microenvironment generated within and surrounding the NICHE, with emphasis on the parameters related to molecular transport. Second, we longitudinally studied the biodistribution of ovalbumin, cytotoxic T lymphocyte-associated antigen-4-Ig (CTLA4Ig), and IgG delivered locally via NICHE over 30 days. Third, we used our findings to develop a physiologically-based pharmacokinetic (PBPK) model. Despite dense and mature vascularization within and surrounding the NICHE, we showed sustained orders of magnitude higher molecular drug concentrations within its microenvironment as compared to systemic circulation and major organs. Further, the PBPK model was able to recapitulate the biodistribution of the 3 molecules with high accuracy (r ​> ​0.98). Overall, the NICHE and the PBPK model represent an adaptable platform for the investigation of local immunomodulation strategies for a wide range of biomedical applications. Graphical abstract: Image 1 Highlights: Confining immunotherapeutics onsite provides maximal immune control. NICHE is a locally immunoprotected platform enabled by in situ drug delivery. NICHE localizes immunotherapeutics with minimal systemic dissemination. PBPK modeling confirmed in vivo localized biodistribution. NICHE and PBPK model are adaptable frameworks for assessing local immunomodulation.